Tradespeak : an interdisciplinary study of business communication in international trade deals : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Business Studies at Massey University - Stoeckl, Birgit Daniela (Massey University, 1997)
In the course of history, English has become the dominant lingua franca of intercultural interaction. About 600 million people world wide are either English native speakers or have at least some speaking ability in the English language.¹ Naoki Kameda, Jeremiah Sullivan, "English as the lingua franca of the Far East", in: Multinational Business Review, 4 (1) Spring 1996, pp. 52 - 62 [ABI-Database copy], p. 5. With its basic inflection system, English has proved to be particularly accommodating to second language learners. It is a well adaptable language. English has been also called a "hybrid language² Kameda, Sullivan, p. 10. giving its speakers the freedom and flexibility in use for their special purposes, especially business purposes. Business English is regarded as a key advantage and necessary condition for export oriented development and upward mobility in Asia.³ Anonymous, "Britannia rules Asia's soundwaves", in: Corporate Location (ABI-Database copy), p.1. It is important to stress that these modified versions of English are "(...) by no means [to be classified as] a pidgin speech. A pidgin English is a ludimentary impoverished use of English arising in situations when parties do not share a common language and when accurate grammatical English is not important."⁴ Kameda, Sullivan, p. 10. Opinions diverge as to whether the feature 'accurate grammatical English' distinguishes Business English from pidgin English.. On the one hand, the view is held that only a balanced bilingualism enables successful and effective communication. English language assessment tests ( TOEFL, TOEIC), for example, aim at determining a profile of the English proficiency required for educational purposes (TOEFL) or different job positions in a company (TOEIC)⁵ Matthew Sindlinger, "An international business language", in Business Mexico, 4 (1,2), 1994 [ABI-Database copy, p. 1].. On the other hand, there is the 'insider opinion' of regarding problem solving skills and flexibility in language use as more relevant than abiding by rigid grammar rules and conventions. [From Introduction]
Keywords: English language; Business English; Business communication; Linguistics; Communication in international trade